OPTIMALISASI PENDAPATAN ASLI DESA MENURUT UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Waspada, Sidik Sakti Indera; Maharani, Andina Elok Puri (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2019)
Law Number 6 of 2014 regulates villages in which there is a regulation regarding original income. The purpose of this study is to analyze the optimization of original village income based on Law Number 6 of 2014 concerning Villages. This journal is a type of qualitative descriptive research. Data collection was carried out by field studies and literature to obtain primary and secondary data with qualitative descriptive analysis methods. From the results of the study, it was concluded that Law No. 6 of 2014 concerning Villages had set the Optimization of original village income. Klopoduwur village has not yet optimized its income regarding village results because the management of original village income is not following the principles of income management in the Law